Domestic violence and associated factors among pregnant women in sub-Saharan African countries from the recent demographic and health survey data: a multilevel analysis - Melkam, Mamaru; Fentahun, Setegn; Rtbey, Gidey; Andualem, Fantahun; Nakie, Girum; Tinsae, Techilo; Wassie, Yilkal Abebaw; Lemma Seifu, Beminate; Fente, Bezawit Melak (Frontiers in Public Health, 2024)
Abstract Introduction: Intimate partner violence is a human rights violation that often involves violence against women, which appears to be the most prevalent type of abuse. Intimate partner violence is a global public health issue with major human rights violations. Pregnant women's intimate partner violence needs special consideration because of the possible harm that might happen to mothers and their fetuses. The enormous global public health issue of intimate partner violence affects physical, mental, and sexual transgressions. Even though there were studies conducted on intimate partner violence among women few studies are conducted among pregnant women in Sub-Saharan Africa countries. Therefore this study revealed intimate partner violence and associated factors among pregnant women from the recent Demographic and Health Survey in Sub-Saharan African countries. Methods: Multilevel logistic regression analysis employed data from the recent Sub-Saharan African countries Demographic and Health Survey was carried out using this secondary data. For this study, pregnant women between the ages of 15 and 49 were included; the total sample size was 17,672. Multilevel logistic regression models were calibrated to determine the associated factors at the individual and community level with intimate partner violence with a 95% CI and AOR. Results: The prevalence of intimate partner violence among pregnant women in 23 Sub-Saharan African countries was 41.94% with a 95% CI of 40.82% to 43.06%. Poorer and poorest [AOR=1.92; 95% CI: (1.01, 3.67)] and [AOR=2.01; 95% CI:(1.02, 3.92)] respectively, partner alcohol drink [AOR=3.37;95% CI:(2.21, 5.14)], and no partner education [AOR=2.01;95% CI:(1.12, 3.63)] were statistically associated factors with intimate partner violence among pregnant women. Concussion: The prevalence of intimate partner violence among pregnant women in Sub-Saharan African countries was high (41.94%). Low economic status, partner drinking alcohol, and partner no education were the associated factors of intimate partner violence. This finding provides clues for policymakers and other organizations concerned about women. Keywords: Intimate Partners Violence, multilevel, and Sub-Saharan Africa.